2020
DOI: 10.1111/aepr.12321
|View full text |Cite
|
Sign up to set email alerts
|

Total‐Factor Energy and Emission Efficiencies of ASEAN and Other Asian Economies

Abstract: This research uses the slack‐based measure data envelopment analysis to compute the energy and emission efficiencies of Association of Southeast Asian Nations (ASEAN) and other Asian economies during the 2001–2017 period, employs the Malmquist productivity index to check for the main source of efficiency score changes due to technical changes, and then applies panel Tobit regressions to determine the factors explaining the efficiencies. Our empirical results show that the energy efficiency scores of ASEAN econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We determine the trends in group energy efficiency for ASEAN and the other six countries not in ASEAN, and although an energy efficiency gap is found to exist between the two groups, the energy efficiency trends of both groups are found to be similar, with the one exception of 2011 to 2012. Hu et al (2021) also indicated that the patterns of energy efficiency in members of ASEAN and other countries not in ASEAN are similar. As illustrated in Figure 2, the energy efficiency of ASEAN members has consistently exhibited greater improvement than that of the other six countries, which is a finding similar to that of Chang (2015) who noted that for countries experiencing rapid economic growth, the potential for improvements in energy intensity is always going to be greater than that in the more developed countries.…”
Section: Results Of Energy Efficiency and Energy Efficiency Changementioning
confidence: 88%
See 2 more Smart Citations
“…We determine the trends in group energy efficiency for ASEAN and the other six countries not in ASEAN, and although an energy efficiency gap is found to exist between the two groups, the energy efficiency trends of both groups are found to be similar, with the one exception of 2011 to 2012. Hu et al (2021) also indicated that the patterns of energy efficiency in members of ASEAN and other countries not in ASEAN are similar. As illustrated in Figure 2, the energy efficiency of ASEAN members has consistently exhibited greater improvement than that of the other six countries, which is a finding similar to that of Chang (2015) who noted that for countries experiencing rapid economic growth, the potential for improvements in energy intensity is always going to be greater than that in the more developed countries.…”
Section: Results Of Energy Efficiency and Energy Efficiency Changementioning
confidence: 88%
“…However, in order to achieve the agreement’s emission reduction level, the short-term strategy of members of ASEAN should pay attention to avoid the reduction of forest area caused by over-development. Hu et al (2021) also mentioned that decreases in the fossil fuel ratio of net electricity generation enhance energy efficiency for ASEAN. In the medium term and long term, we suggest that the governments of ASEAN+6 should not only improve energy efficiency by attracting foreign-funded energy service companies (ESCOs) through policy subsidies or investment promotion, but also cooperate with academic institutions to jointly develop renewable energy resources to reduce the level of fossil fuel energy use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, Asian economies relied on input-driven growth, which has resulted in slow growth rates due to the law of diminishing returns and the use of energy-inefficient technology and equipment [8]. Improving energy efficiency is critical for sustaining Asia's economic growth [9]. Asia's energy demand has increased sharply because more people are living in cities, incomes are increasing, and the continent is becoming more industrialized [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al [6] assessed the environmental efficiency of South Asia. Hu et al [9] centered their attention on the total factor energy efficiency (TFEE) and emission efficiencies of the Association of South East Asian Nations (ASEAN) and non-ASEAN economies. Therefore, this paper will add to the body of knowledge by analyzing the total factor energy efficiency and total factor carbon emission efficiency (TFCEE) of selected Asian countries.…”
Section: Introductionmentioning
confidence: 99%